1991
DOI: 10.1111/j.1365-2141.1991.tb04528.x
|View full text |Cite
|
Sign up to set email alerts
|

The high molecular weight form of endothelial cell von Willebrand factor is released by the regulated pathway

Abstract: We have previously reported that two forms of von Willebrand factor (vWf) exist in cultured human umbilical vein endothelial cells: a high molecular weight (HMW) form that is released and can be proteolytically cleaved into a series of plasma-like multimers, and a non-secreted low molecular weight (LMW) form. In this study, the mode of vWf release and the relationship between the two forms were examined. As determined by two-dimensional analysis as well as by immunoreactivity with an antibody to the propolypep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 15 publications
4
47
0
1
Order By: Relevance
“…6 WPBs store VWF for regulated secretion upon endothelial activation, but they can also fuse and release VWF in the absence of activation, a process termed "basal" secretion to distinguish it from "constitutive" secretion, 7,8 although both collect together in the supernatant of unstimulated cells. Low-molecularweight-VWF (LMW-VWF) is secreted by the constitutive pathway, in contrast to the HMW-VWF released via stimulated WPBs, 6,9 consistent with the need to control release of highly prothrombotic material.…”
Section: Introductionmentioning
confidence: 95%
“…6 WPBs store VWF for regulated secretion upon endothelial activation, but they can also fuse and release VWF in the absence of activation, a process termed "basal" secretion to distinguish it from "constitutive" secretion, 7,8 although both collect together in the supernatant of unstimulated cells. Low-molecularweight-VWF (LMW-VWF) is secreted by the constitutive pathway, in contrast to the HMW-VWF released via stimulated WPBs, 6,9 consistent with the need to control release of highly prothrombotic material.…”
Section: Introductionmentioning
confidence: 95%
“…Possibly these precursors will never form mature WPBs but are destined for constitutive release as low molecular weight multimers, or for degradation. Indeed, it has been reported that between 90% (Tsai et al, 1991) and 10% (Sporn et al, 1986) of VWF is secreted constitutively, and that such material is of lower molecular weight than that released from WPBs by regulated exocytosis. Subunits may, alternatively, be able to organise themselves into tubules after they have left the Golgi.…”
Section: Tubule Subunitsmentioning
confidence: 99%
“…1 Tregs appear to be a relatively rare CD4 ϩ T-cell subset that comprise many subpopulations, including IL-10 -producing "Tr1Ј cells10, TGF-␤-producing T helper type 3 cells, CD8 ϩ T suppressor cells, natural killer T cells, CD4-CD8 -T cells and ␥␦ T cells." [2][3][4][5] Some of these cells originate in the thymus during ontogeny and are referred to as "natural" Tregs. Some Tregs can also be induced from naive T cells in the periphery.…”
Section: Itp Three R's: Regulation Routing Rituximab --------------mentioning
confidence: 99%
“…They are critical to our survival, and absence of them can lead to either autoimmunity or inflammatory disorders, with fatal consequences in both mice and humans. [1][2][3][4][5] Although defects of these cell types have previously been described in immune thrombocytopenic purpura (ITP), 7-9 3 papers in this issue collectively suggest that a deficient Treg compartment allows enhanced T-cell and B-cell autoreactivity in ITP, and that therapies like rituximab actually correct the deficiency and reverse autoimmune platelet reactivity, thus leading to increased platelet counts.…”
Section: Itp Three R's: Regulation Routing Rituximab --------------mentioning
confidence: 99%